Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Agresivitas Pajak Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2018-2020 - Putu Satia Dewi; Ni Luh Putu Mita Miati (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2026)
This study examines the effect of liquidity, leverage, and firm size on tax aggressiveness among manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research employs a quantitative approach using secondary data obtained from annual reports of manufacturing firms for the 2018–2020 period. The sample was selected through purposive sampling, resulting in 64 firms and a total of 192 firm-year observations. Multiple linear regression analysis was applied to test the relationship between the independent variables—liquidity, leverage, and firm size—and the dependent variable, tax aggressiveness. The results indicate that liquidity, leverage, and firm size each have a positive and significant effect on tax aggressiveness. These findings suggest that firms with higher liquidity levels, greater leverage, and larger organizational scale are more likely to engage in tax aggressiveness practices. The study contributes to the literature on corporate taxation by providing empirical evidence on the determinants of tax aggressiveness in Indonesian manufacturing firms.